2012
DOI: 10.1007/s12040-012-0141-6
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in biomass and species composition of seaweeds along the northern coasts of Persian Gulf (Bushehr Province)

Abstract: This study was carried out to evaluate the seasonal variations of seaweed biomass and species composition at six different sites along the coastal areas in Bushehr Province. Sampling depths varied among sites, from 0.3 to 2.0 m below mean sea level. A total of 37 (i.e., 10 Chlorophyta, 12 Phaeophyta and 15 Rhodophyta) seaweed species were collected. Studies were conducted for quantifying the seaweeds during four seasons from October 2008 until July 2009. During present research, Ulva intestinalis and Cladophor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 8 publications
2
3
0
2
Order By: Relevance
“…This resut is not unexpected and has been previously documented (Thongroy et al 2007;Raffo et al 2014). Moreover, the values of the Shannon-Wiener diversity index (H') obtained in this study (between 1.11 and 1.95) were considerably lower than those of Dadolahi-Sohrab et al, (2012) reported from the northern coasts of Persian Gulf in Bushehr province (between 2.28 and 2.87). Both urbanization and substratum can cause such a low diversity in the eastern coast of Qeshm Island.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This resut is not unexpected and has been previously documented (Thongroy et al 2007;Raffo et al 2014). Moreover, the values of the Shannon-Wiener diversity index (H') obtained in this study (between 1.11 and 1.95) were considerably lower than those of Dadolahi-Sohrab et al, (2012) reported from the northern coasts of Persian Gulf in Bushehr province (between 2.28 and 2.87). Both urbanization and substratum can cause such a low diversity in the eastern coast of Qeshm Island.…”
Section: Discussionsupporting
confidence: 81%
“…Hence, the result of this study which showed the highest biomass of macroalgae in winter may be attributable to increased nutrient availability in this season. Dadolahi-Sohrab et al, (2012) also demonstrated that the period of maximum algal growth is late winter to mid-summer along the northern coasts of the Persian Gulf. In our study, the BIOENV analysis indicated chemical parameters (TDS and pH) as significantly influencing the macroalgal communities along the easthern cost of Qeshm Island.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Alga coklat memiliki kemampuan untuk beradaptasi karena memiliki lapisan lendir (mucus) yang dapat mengatasi kekurangan air, serta memiliki toleransi terhadap pasang surut yang lebih lama (Dadolahi-Sohrab et al, 2012), sehingga pada perairan Ujung Genteng distribusinya dapat ditemukan berada pada ketiga kawasan pengamatan. Jenis alga yang paling banyak ditemukan di kawasan perairan Ujung Genteng adalah alga merah, yaitu 13 jenis ditemukan di kawasan-2, 11 jenis di kawasan-3, dan sembilan jenis di kawasan-1.…”
Section: Hasil Dan Bahasan Distribusi Rumput Laut Alamunclassified
“…Jenis rumput laut yang berbeda akan memiliki kemampuan terbaik agar bisa bertahan Gambar 3. Rata-rata tutupan substrat dasar perairan pada tiga kawasan pengamatan di perairan Ujung Genteng, Jawa Barat (L: lamun, P: pasir, K: karang hidup, PK: pecahan karang, BK: batu karang, SW: seaweed) (huruf yang berbeda menunjukkan hasil uji yang berbeda nyata (P<0,05)) di lokasi yang berbeda dengan cara seoptimal mungkin (Dadolahi-Sohrab et al, 2012).…”
Section: Karekteristik Substrat Dasar Perairanunclassified